The Brookings and Tucker Estimates: Further Comments - Hagen, Everett E. (The Review of Economics and Statistics, 1945)
prewar trends had continued. The war only made them go to work a few years earlier. I remain convinced therefore that, although my estimates of the labor force and the amount of civilian employment are lower than the others quoted by Mr. Hagen, they are more nearly correct. As for gross national product, the sooner statisticians and economists discontinue treating that misleading monetary concept as if it were equivalent to the real national product or the output of workers or the national welfare, the better for all concerned.